2012
DOI: 10.1063/1.3673571
|View full text |Cite
|
Sign up to set email alerts
|

Negative Magnus lift on a rotating sphere at around the critical Reynolds number

Abstract: Maximum entropy states of quasi-geostrophic point vortices Phys. Fluids 24, 056601 (2012) Effect of swirl decay on vortex breakdown in a confined steady axisymmetric flow Phys. Fluids 24, 043601 (2012) Simulations of turbulent rotating flows using a subfilter scale stress model derived from the partially integrated transport modeling method Phys. . The numerical methods used were first validated on a non-rotating sphere, and the spatial resolution around the sphere was determined so as to reproduce the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 17 publications
5
41
1
1
Order By: Relevance
“…Meanwhile, the second-order central difference scheme is used for the spatial derivatives with 5 % of the first-order upwind scheme being blended for the calculation of the convection term for the sake of numerical stability. For the time advancement, the first-order Euler implicit scheme is used, which coincides with the corresponding scheme in Muto's [10] work. According to the estimation provided by Muto et al [10], the simulation results showed very limited difference between the first-order Euler scheme and the third-order Adams-Moulton scheme when relatively fine meshes were allocated around the sphere and the Courant number was kept to be less than 1.8.…”
Section: Numerical Methods and Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the second-order central difference scheme is used for the spatial derivatives with 5 % of the first-order upwind scheme being blended for the calculation of the convection term for the sake of numerical stability. For the time advancement, the first-order Euler implicit scheme is used, which coincides with the corresponding scheme in Muto's [10] work. According to the estimation provided by Muto et al [10], the simulation results showed very limited difference between the first-order Euler scheme and the third-order Adams-Moulton scheme when relatively fine meshes were allocated around the sphere and the Courant number was kept to be less than 1.8.…”
Section: Numerical Methods and Conditionsmentioning
confidence: 99%
“…They provided insight into both the statistical features, such as the prediction of the mean drag force, and the instantaneous features including how the aerodynamic forces developed over time. Muto et al [10] extended the numerical work to the research on a rotating sphere. In this study, Large-eddy simulations (LES) were conducted for a sphere in both stationary and rotating conditions, and the phenomenon that a lift force pointing to the direction opposite to the one suggested based on the potential theory, which is namely the negative or inverse Magnus effect, was successfully reproduced and its physical mechanism was discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Webb (1993) investigated the swimming performance of steelhead trout in channels with solid or porous walls and highlighted the wall effect on kinematics. However, considering the relatively low Reynolds number in this study, the effect is considered (Muto, Tsubokura, & Oshima, 2012; http:// www.ciss.iis.u-tokyo.ac.jp/rss21/), which adopts an unstructured finite-volume procedure with vertex-cen tered-type storage on a grid. The third-order upwind difference scheme is used to discretize the spatial derivatives.…”
Section: Schematic Diagram Formulamentioning
confidence: 99%
“…Note that for all three test cases, the grid resolution in the wall-normal (y) direction is the same as that of the original DNS data. A posteriori calculations were performed using an unstructured finite-volume procedure that was almost the same as that used by Muto et al (2012), where vertex-centered type storage was used on a grid. The second-order central difference scheme was used to discretize the spatial derivatives except for the convection term of k S GS (Eq.…”
Section: Test Cases and Computational Conditionsmentioning
confidence: 99%